PROPAGANDA TURKI TERHADAP ISRAEL (STUDI KASUS FILM VALLEY OF THE WOLVES: PALESTINE 2011) - Ahmad Fauz; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is discussing a propaganda Israel through Turkey on Valley ofthe Wolves: Palestine in 2011. The movie telling a story of assaulting MaviMarmara ship by Israel and raising the phenomenon conflict of Israel-Palestinian. The research uses qualitative method according libraries systemof study. The author applying constructivism as perspective and propagandatheory of Harold Dwight Lasswell in explain significance Turkey through theValley of the Wolves: Palestine. In this study it was found that Turkey wasdeliberately released the movie with propaganda. Turkey’s effort to showIsrael’s negative image as an instrument in order to gain sympathy andsupport for the Palestinians primarily through human right violations in MaviMarmara incident. Turkey also has interests that created the politicalinfluence in the Middle East by adopting a policy of orienting the Arabcountries and carried out through various approaches, support Palestinianindependence depicted on the movie Valley of the Wolves: Palestine.Keywords : Propaganda, Support, Interest, Valley of the Wolves: Palestine